Managing Supply Chain Risk - Sodhi, ManMohan S.; Tang, Christopher S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
“Supply Chain Risk Management is an issue that many companies face and yet few companies know how to deal with it in a systematic and pragmatic manner. While avoiding and reducing supply chain risks are certainly preferable, developing ways to restore and stabilize supply chain operations rapidly after a major disruption is critical for managing global supply chains. Sodhi and Tang present important concepts, frameworks, strategies, and analyses that are essential for managing supply chain risks. Not only does this book suggest some practical ways to work with different partners to manage the risks that are present in a global supply chain, it creates a framework that would enable practitioners to engage researchers to work on this important area.” —Thomas A. Debrowski, Executive Vice President, Worldwide Operations, Mattel, Inc.
Supply Chain Risk Management -- Risk Identification -- Risk Assesment -- Mitigating Risks -- Response as a Mitigation Approach -- How do Global Manufacturing Companies Mitigate Supply Chain Risks -- Strategic Approaches for mitigating Supply Chain Risks -- Tactical Approaches for Mitigating Supply Chain Risks: Financial and Operational Hedging -- Application - Scenario Planning for Mitigating Supply Chain Restructuring Risk at a PVC Manufacturer -- Application - Mitigating Outsourcing-Related Risks -- Application - Mitigating New Product Development Risks - The Case of the Boeing 787 Dreamliner -- Application - Managing Product Recalls - The Case of Mattel, Inc -- Risk Models for Supply Chain Management -- Modeling the Vaule of Flexibility -- Stochastic Programming for Supply Chain Planning Under Demand Uncertainty -- Researchers' Prespectives on Supply-Chain Risk Research -- Conclusion and Future Research.
Keywords: Production management; Engineering economics; Engineering economy; Operations research; Decision making; Operations Management; Engineering Economics, Organization, Logistics, Marketing; Operations Research/Decision Theory